Immune-checkpoint inhibitors and metastatic prostate cancer therapy: Learning by making mistakes. (August 2020) - Claps, Mélanie; Mennitto, Alessia; Guadalupi, Valentina; Sepe, Pierangela; Stellato, Marco; Zattarin, Emma; Gillessen, Sommer Silke; Sternberg, Cora N.; Berruti, Alfredo; De Braud, Filippo Guglielmo Maria; Verzoni, Elena; Procopio, Giuseppe
Highlights: Metastatic castration resistant prostate cancer express PD-L1 in 32% of cases. CDK12-mutations could predict response to PD-1/PD-L1 inhibitors. Combinations with vaccines, hormones, PARPi and chemotherapy improved outcomes. Alterations in DDR genes conferred sensitivity to anti-PD-1 combined with PARPi. Abstract: Despite advances in metastatic prostate cancer therapy, expected survival for patients in the castration-resistant phase of disease is poor. Immune-checkpoints inhibitors significantly prolonged life expectancy in some solid tumors and have been evaluated also in advanced stage prostate cancer. The majority of data available derive from preliminary phase I and II trials evaluating CTLA-4 and PD-1 as monotherapy or in combination with each other, vaccines, radiotherapy or targeted/hormonal therapy, achieving only limited benefits in terms of biochemical and radiologic responses. There are many reasons that may explain why prostate cancer responds poorly to modern immunotherapies, such as its characteristic low tumor mutational burden or immune-suppressive tumor microenvironment. The present review summarizes the results obtained treating advanced prostate cancer patients with immune-checkpoints inhibitors and analyzes potential mechanisms of both resistance and sensitivity, in order to hypothesize possible avenues of special interest for future research.